PENGARUH SOCIAL MEDIA MARKETING DAN CUSTOMER BONDING TERHADAP CUSTOMER LOYALTY PADA JEGEG GLOWING - SARASWATI, GUSTI AYU KADEK; KUSUMA, GUSTI PUTU EKA; NURKARIANI, NI LUH (Universitas Mahasaraswati K. Mataram, 2023)
The purpose of this research is to determine the influence of Social Media Marketing and Customer Bonding on Customer Loyalty. This research was conducted on Jegeg Glowing beauty treatments, data collection techniques used a questionnaire. The samples taken were 64 customers. The data analysis techniques used are multiple linear regression, determination analysis and hypothesis testing with the t test. data analysis with SPSS 29.0 for windows. The research results show 1) Social Media Marketing has a positive and significant effect on customer loyalty with a value of tcount > ttable (3.006>1.999) with a significance value = 0.004. If you use a significance level of 0.05, it can be concluded that 0.004 < 0.05. 2) Customer Bonding has a positive and significant effect on Customer Loyalty at Jegeg Glowing tcount>ttable (6.314>1.999) with a significance value = 0.001. If you use a significance level of 0.05, it can be concluded that 0.001 < 0.05. 3) and the results of the f test calculation obtained fcount>ftable, (42.074>3.148) showing that Social Media Marketing and Customer Bonding together influence Customer Loyalty at a level of 0.001<0.05